2014
DOI: 10.1039/c4ra04861j
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and characterization of ZrO2nanoparticles prepared by the AOP/hydrothermal route

Abstract: We report on the synthesis and characterization of ZrO 2 nanoparticles prepared from zirconium(IV) butoxide in the absence of base or acid mineraliser by an advanced oxidation processes (AOP) and subsequent hydrothermal treatment which involves mixing and dissolution of the precursor for different temperatures. The structure, morphology and properties of the nanoparticles were characterized using XRD, FE-SEM, TEM, HRTEM, Raman spectroscopy, FT-IR spectroscopy, BET measurements and TGA measurements. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…The ZrO 2 nanoparticles modified CPE was characterised by first studying the sizes of the ZrO 2 nanoparticles using a Zetasizer. The sizes were recorded and ranged between 20 to 470 nm, which is in line with other works in the literature, where their synthesis produced sizes ranging from 10 to 400 nm [39,40].…”
Section: Characterisation Of the Zro 2 Nanoparticlessupporting
confidence: 88%
See 1 more Smart Citation
“…The ZrO 2 nanoparticles modified CPE was characterised by first studying the sizes of the ZrO 2 nanoparticles using a Zetasizer. The sizes were recorded and ranged between 20 to 470 nm, which is in line with other works in the literature, where their synthesis produced sizes ranging from 10 to 400 nm [39,40].…”
Section: Characterisation Of the Zro 2 Nanoparticlessupporting
confidence: 88%
“…in line with other works in the literature, where their synthesis produced sizes ranging from 10 to 400 nm [39,40]. SEM provides information on the external morphology, chemical composition, and crystalline structure of the ZrO2 nanoparticles.…”
Section: Characterisation Of the Zro 2 Nanoparticlessupporting
confidence: 85%
“…Padovini et al [54] analyzed a hydrothermal zirconia nanoparticle synthesis and found that ZrO 2 nanoparticles directly formed amorphous microspheres before the primary particles crystallized within these structures.…”
Section: Factors Affecting the Agglomerationmentioning
confidence: 99%
“…Furthermore, the values are also in good agreement with other specific surface area values reported for ZrO 2 nanoparticles in the literature. 53,54 Verma et al synthesized ZrO 2 nanoparticles using a reactive magnetron sputtering technique and were able to adjust the specific surface area from 119.81 to 48.89 m 2 g −1 by a subsequent annealing treatment at different temperatures. Here, adjusting the specific surface area of the nanoparticles can be achieved directly through controlling the growth conditions by temperature.…”
Section: Influence On Nanoparticle Propertiesmentioning
confidence: 99%